Nobody's gonna slow me down? - Branco, Catarina (2023)
Funding Information: ☆ The authors are grateful to Kristian Behrens (the editor), two anonymous referees, Pedro Bação, Ronald Bachmann, Pedro Pita Barros, Samira Barzin, Mário Centeno, Joana Costa, Dave Donovan, Luisa Doerr, Ed Glaeser, Robert Gold, Nezih Guner, Julian Hinz, Adelheid Holl, Gabriel Kreindler, Xiang Li, Pedro Martins, Alejandro Micco, Yi Niu, Susana Peralta, Alfredo M Pereira, Miguel Portela, Pedro Portugal, Francisco Queiró, Lasare Samartzidis, Rok Spruk, and seminar participants at Nova SBE, the DUP meeting (Harvard University), the 3rd CompNet ProdTalks, SAEe2020, the 9th PhD Student Workshop on Industrial and Public Economics (ECO-SOS), the 10th European Meeting of the UEA, COMPIE 2021, the 14th Annual Meeting of the PEJ, EARIE 2021, Jornadas de Economia Industrial of the Spanish Economic Association, 11th ifo Dresden Workshop on Regional Economics, CAED 2021 (Coimbra), the 4th Meeting on Transport Economics and Infrastructure, the Fourth International Workshop “Market Studies and Spatial Economics”, the Spring Meeting for Young Economists (Orléans), the 7th Linked Employer-Employee Data Workshop (FEP), and the 2022 SMU-Jinan Conference on Urban and Regional Economics for useful comments and suggestions. We would also like to thank BPLim – Banco de Portugal for providing the necessary data for this study and Nuno Afonso for excellent research assistance. This work was funded by Fundação para a Ciência e Tecnologia (UIDB/00124/2020, UIDP/00124/2020 and Social Sciences DataLab - PINFRA/22209/2016), POR Lisboa and POR Norte (Social Sciences DataLab, PINFRA/22209/2016). All errors are our own. Funding Information: The authors are grateful to Kristian Behrens (the editor), two anonymous referees, Pedro Bação, Ronald Bachmann, Pedro Pita Barros, Samira Barzin, Mário Centeno, Joana Costa, Dave Donovan, Luisa Doerr, Ed Glaeser, Robert Gold, Nezih Guner, Julian Hinz, Adelheid Holl, Gabriel Kreindler, Xiang Li, Pedro Martins, Alejandro Micco, Yi Niu, Susana Peralta, Alfredo M Pereira, Miguel Portela, Pedro Portugal, Francisco Queiró, Lasare Samartzidis, Rok Spruk, and seminar participants at Nova SBE, the DUP meeting (Harvard University), the 3rd CompNet ProdTalks, SAEe2020, the 9th PhD Student Workshop on Industrial and Public Economics (ECO-SOS), the 10th European Meeting of the UEA, COMPIE 2021, the 14th Annual Meeting of the PEJ, EARIE 2021, Jornadas de Economia Industrial of the Spanish Economic Association, 11th ifo Dresden Workshop on Regional Economics, CAED 2021 (Coimbra), the 4th Meeting on Transport Economics and Infrastructure, the Fourth International Workshop “Market Studies and Spatial Economics”, the Spring Meeting for Young Economists (Orléans), the 7th Linked Employer-Employee Data Workshop (FEP), and the 2022 SMU-Jinan Conference on Urban and Regional Economics for useful comments and suggestions. We would also like to thank BPLim – Banco de Portugal for providing the necessary data for this study and Nuno Afonso for excellent research assistance. This work was funded by Fundação para a Ciência e Tecnologia (UIDB/00124/2020, UIDP/00124/2020 and Social Sciences DataLab - PINFRA/22209/2016), POR Lisboa and POR Norte (Social Sciences DataLab, PINFRA/22209/2016). All errors are our own. Publisher Copyright: © 2023 The Author(s)